(untitled) (INNOVATIVE ECONOMY, 2023)
Kovshova I.A., Savchenko K.A. THE IMPACT OF CONSUMER FATIGUE FROM MAKING DECISION ON THE FORMATION OF BRAND LOYALTY Purpose. The purpose of the article is the formation of theoretical, methodological and practical foundations for the implementation of marketing tools to assess the impact of consumer fatigue from making everyday decisions on brand loyalty and purchasing behaviour in stores. Methodology of research. The theoretical and methodological basis of the article was formed by the provisions of behavioural economics, neuro-marketing, and branding. The study is based on the dialectical method of learning the influence of consumer fatigue from decision-making on brand loyalty. General scientific and special methods are used within the limits of the mentioned approach, in particular: comparison – to determine the advantages and disadvantages of different groups of marketing tools; questionnaire survey – for a pilot study of the criteria for making a decision on the purchase of goods by consumers in stores; mathematical modelling – for evaluating the data obtained during the experiment and determining the tendencies of choosing the company’s product or brand by consumers during fatigue; analysis and synthesis – to form a mechanism for the implementation of neuro-marketing tools by companies; induction and deduction – to interpret conclusions based on research results. Findings. The phenomenon of consumer decision fatigue resulting from repeated choice-making is explored, leading to mental exhaustion and impaired behaviour control, affecting brand loyalty. A concept is formulated for the application of neuro-marketing tools to understand consumer behaviour in retail stores, which engages all human sensory organs, including audio influence, visualization, tactile stimulation, scent influence, and taste stimulation. Pilot study of the purchasing behaviour of consumers in a state of physical or mental fatigue and without it was conducted. It has been established that closer to the evening, consumer fatigue from decision-making is observed, as during the day people may be under the influence of stressful factors, depleting emotional and cognitive resources. The factors that are important in making a decision regarding the choice of a product of a certain brand are singled out. The hypothesis regarding the influence of consumer fatigue from decision-making on the formation of brand loyalty was confirmed. Originality. The concept is formulated of using neuromarketing tools for a better understanding of consumer behavior in stores, a more detailed analysis of the decision-making process and their purchasing behavior, the formation of habits and loyalty to company brands, consumer reactions to product packaging and labeling in a state of fatigue. Practical value. The results of the pilot study will help create more effective marketing campaigns using a personalized approach to consumers and simplified communication. Key words: consumer behaviour, decision fatigue, marketing, shopping in stores, brand loyalty, neuro-marketing.